Laser applications in surface science and technology - Rubahn, H.-G. (Horst-Günter) (John Wiley & Sons, 1999)
Laser Applications in Surface Science and Technology provides an overview of the different techniques, discusses the principles behind them and gives a concise description of laser-induced and laser-detected processes on surfaces. Recent developments in the field such as nonlinear surface spectroscopies and the interactions of ultrashort pulses with materials are also introduced. Invaluable reading for postgraduate students and research scientists across a wide range of disciplines including: physics, chemistry, electronic engineering and materials science.